Pengembangan E-Modul Berbasis Etnosains Terintegrasi Tri–N untuk Meningkatkan Dimensi Kreatif Peserta Didik Kelas V Sekolah Dasar - Septi, Sam Wulan; Masjid, Akbar Al (Jurnal Studi Guru dan Pembelajaran, 2025)
The urgency of this research lies in the lack of contextual and culturally-based learning media to enhance students' creativity in IPAS learning. This study aims to develop an ethnoscience-based e-module integrated with the Tri-N approach (Niteni, Nirokke, Nambahi) to enhance the creative dimension of fifth-grade elementary school students. The development process followed the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. During the analysis phase, it was found that students require an interactive learning medium that connects IPAS subject matter, particularly the topic of light properties, with local wisdom, such as the traditional wayang kulit purwa shadow puppet performance. The e-module was designed with key characteristics: self-instructional, self-contained, stand-alone, adaptive, and user-friendly. Validation by media and content experts indicated that the e-module was suitable for use with several revisions, including font size adjustment, image layout refinement, and the addition of interactive QR codes. Trials involving 30 students across four elementary schools showed a significant increase in students’ creative dimensions, with an average score rising from 1.82 to 3.40 (26.4% to 84.8%). Students successfully produced creative works such as wayang performances and simple experiments illustrating light concepts. Further evaluation revealed that the e-module not only strengthened students’ understanding of IPAS concepts but also enhanced their engagement and appreciation of local culture. Both teachers and students responded positively to the module. However, its limitation lies in its specific cultural context, making it most relevant in regions familiar with wayang kulit purwa. Therefore, future development is recommended to adapt the module to various local wisdoms across Indonesia and expand its content to cover other science topics. The results indicate that this Tri-N integrated ethnoscience e-module is an effective and innovative learning tool for fostering creativity and cultural values in elementary science education.